Evidence for functional asymmetry in the olfactory system of the senegalese sole ( solea senegalensis ) - Velez, Zélia (2014)
The two olfactory epithelia of flatfish of the family Soleidae are essentially in contact with two distinct environments; the upper (right) side samples open water while the lower (left) side samples interstitial water. This study assessed whether there are differences in the responsiveness of the two epithelia by use of the electro‐olfactogram in the Senegalese sole (Solea senegalensis). The upper epithelium was significantly more responsive to the basic amino acids (l‐lysine and l‐arginine), glycine, and l‐threonine than the lower epithelium. The lower epithelium was significantly more responsive to aromatic amino acids (l‐tryptophan, l‐tyrosine, l‐DOPA, and l‐phenylalanine), l‐leucine, and l‐asparagine than the upper. Both epithelia had similar responsiveness to the sulphur‐containing amino acids (l‐cysteine and l‐methionine), l‐alanine, l‐serine, and l‐glutamine. Neither side was responsive to the acidic amino acids (l‐aspartate and l‐glutamate) or the D‐isomers of any amino acid tested. The upper olfactory organ was much more responsive to conspecific‐derived stimuli (bile and intestinal fluid) than the lower organ. We suggest that these differences in responsiveness may be related to different functional roles of the upper and lower epithelia in feeding and chemical communication.